(untitled) (MCIT: Proceedings of International scientific and practical conference, 2019)
We study a model of discrete conflict dynamical system with attractive and repulsive interaction, which describes the redistribution of common space of existence between three alternative populations. The evolution of the redistribution of common space of existence is illustrated by examples. It is assume that two populations struggle to survive on a shared space of existence (repulsive interaction), and third coexist with first two ones in the same space (attractive interaction).